The effect of financial soundness variables on bank performance: a macro-level analysis in MSCI Emerging Market Index countries - Arzova, Sabri Burak; Sahin, Bertac Sakir (EMERALD GROUP PUBLISHING LTD, 2024)
PurposeThe present study investigates the impact of financial soundness variables on bank performance in emerging countries.Design/methodology/approachThis study uses macro-level panel data from 17 countries from 2011 to 2020. The analysis adopts six models. While four models include bank profitability, the dependent variable of the other models is Bank Z Scores. Regulatory Capital to Risk-Weighted Assets, Liquid Assets to Total Assets, Non-Performing Loans to Total Gross Loans and Non-Interest Expenses to Gross Income are proxies of financial soundness variables.FindingsThe authors estimate fixed and random effects models with the Arellano, Froot and Rogers methods. Empirical results show that Non-Performing Loans to Total Gross Loans harm ROA and ROE. Regulatory Capital to Risk-Weighted Assets negatively affects ROE. Non-Interest Expenses to Gross Income on Bank Z Scores have a significant and negative effect. Moreover, Inflation, Foreign Direct Investment and GDP are macroeconomic variables that increase bank profitability.Originality/valueThis study contributes to the literature in different aspects. The first is the model of the study. The authors contribute to the literature regarding the variables used to measure financial soundness. Secondly, emerging countries are samples in the study. A significant part of the studies on financial soundness has focused on developed countries. Finally, the authors analyze the macro-level data. Bank soundness studies mainly investigate country-level variables. Macro-level analysis may provide an advantage in combating global financial crises.
Keywords: Financial soundness; Emerging countries; Banking profit; Emerging market bank performance; SCALE-FREE NETWORK; SYSTEMIC RISK; CASCADING FAILURE; INVULNERABILITY; CONNECTEDNESS; Computer Science